2008
DOI: 10.1038/ncb1724
|View full text |Cite
|
Sign up to set email alerts
|

p53 regulates glucose metabolism through an IKK-NF-κB pathway and inhibits cell transformation

Abstract: Cancer cells use aerobic glycolysis preferentially for energy provision and this metabolic change is important for tumour growth. Here, we have found a link between the tumour suppressor p53, the transcription factor NF-kappaB and glycolysis. In p53-deficient primary cultured cells, kinase activities of IKKalpha and IKKbeta and subsequent NF-kappaB activity were enhanced. Activation of NF-kappaB, by loss of p53, caused an increase in the rate of aerobic glycolysis and upregulation of Glut3. Oncogenic Ras-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
522
3
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 566 publications
(554 citation statements)
references
References 29 publications
15
522
3
10
Order By: Relevance
“…In addition to the established role of p53 in cell cycle arrest and apoptosis, recent evidence has demonstrated that p53 reduces glycolytic flux and increases oxidative phosphorylation, halting the Warburg effect. [137][138][139][140][141][142][143] TIGAR (Tp53-induced glycolysis and apoptosis regulator) was identified to function as a fructose-2,6-bisphosphatase (Fru-2,6-BP), antagonizing the third step of glycolysis and thereby redirecting metabolite flux to the pentose phosphate pathway. [138][139][140] Interestingly, basal or low levels of p53 expression have been suggested to provide antioxidant effects and thus elicit cellular protection rather than cell death.…”
Section: Other Modulation Of Mitohk-iimentioning
confidence: 99%
“…In addition to the established role of p53 in cell cycle arrest and apoptosis, recent evidence has demonstrated that p53 reduces glycolytic flux and increases oxidative phosphorylation, halting the Warburg effect. [137][138][139][140][141][142][143] TIGAR (Tp53-induced glycolysis and apoptosis regulator) was identified to function as a fructose-2,6-bisphosphatase (Fru-2,6-BP), antagonizing the third step of glycolysis and thereby redirecting metabolite flux to the pentose phosphate pathway. [138][139][140] Interestingly, basal or low levels of p53 expression have been suggested to provide antioxidant effects and thus elicit cellular protection rather than cell death.…”
Section: Other Modulation Of Mitohk-iimentioning
confidence: 99%
“…Glucose consumption and lactate production in CRC cells were analyzed as previously described (16). Glucose and lactate levels in the culture medium were also determined by using the glucose assay kit and lactate assay kit, respectively.…”
Section: Measurement Of Glucose and Lactatementioning
confidence: 99%
“…81,82 Loss of p53 activity Different regulators in healthy tissues control the glucose metabolism, including p53, AKT, Myc and HIF proteins. P53, in particular, inhibits the expression of glucose transporters (GLUTs), such as GLUT1 and GLUT4 83 or GLUT3, 84 and reduces glucose utilization in the glycolytic pathway [85][86][87] (Fig. 3).…”
Section: Deliberate Activation Of Rtk Pathwaysmentioning
confidence: 99%